Overexpression of Toll-Like Receptor 4 Contributes to Phagocytosis of Salmonella Enterica Serovar Typhimurium via Phosphoinositide 3-Kinase Signaling in Sheep - Sutian Wang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Phagocytosis of bacteria by monocytes/macrophages can trigger the immune response and the clearance of bacteria. This innate immune response involves Toll-like receptor 4 (TLR4). However, much remains unknown about the mechanism of TLR4-regulated phagocytosis of Salmonella enterica serovar Typhimurium (S. typhimurium) within sheep monocytes/macrophages. Here, we aimed to address these knowledge gaps by infecting transgenic sheep overexpressing TLR4 with S. typhimurium and examining the phagocytic mechanisms involved. Methods: Transgenic sheep were generated by microinjection of the constructed plasmids into fertilized eggs. Monocytes/macrophages isolated from sheep blood were stimulated with LPS and S. typhimurium. Phagocytosis-related factor expression, phagocytic ability, and adhesion were then determined. TLR4/phosphatidylinositide 3-kinase (PI3K) signaling was inhibited to investigate if this pathway is involved in changes in bacterial internalization in sheep. Results: We found that TLR4 overexpression effectively activated the PI3K signaling pathway and upregulated the expression of scavenger receptors. Additionally, actin polymerization and adhesive capacity were both enhanced in TLR4-overexpressing sheep monocytes/macrophages. TLR4 inhibition decreased S. typhimurium phagocytosis by reducing the actin polymerization and adhesive capacity of cells. Furthermore, inhibition of PI3K markedly impaired TLR4-dependent phagocytosis by restraining actin polymerization and scavenger receptor expression and reduced the adhesive capacity of the monocytes/macrophages. Conclusion: Our findings indicate that overexpression of TLR4 enhances phagocytosis through PI3K signaling and the subsequent activation of actin polymerization and scavenger receptors in sheep monocytes/macrophages infected with S. typhimurium.